Trend of snow cover under the influence of climate change using Google Earth Engine platform: A case study of Astore (Western Himalayas) and Shigar (Karakoram region) - Moazzam, Muhammad Farhan Ul; Rahman, Ghani; Lee, Byung Gul; Ansari, Nadhir Al (Frontiers in Environmental Science, 2022)
Freshwater resources present in Upper Indus Basin (UIB) supply water to Pakistan’s irrigation. Half of the annual water discharge in the UIB is contributed from the glacier and snow-fed basins in the Hindu Kush, Karakoram, and Himalaya (HKH) region and it is currently under threat of climate change. Therefore, it is very necessary to study and monitor the spatiotemporal changes in snow cover area (SCA) and its response to climate variables to efficiently manage water reservoirs. Thus, keeping this problem in mind we conducted this study using Google Earth Engine Application Programming Interface (GEE API) for Astore and Shigar. We have used mean annual Landsat data between 1991 and 2021 to derive the SCA using normalized difference snow index (NDSI). ASTER GDEM data was used to extract the elevation and analyze the distribution of SCA on different elevation zones. Eventually, we used the climate research unit (CRU) data (rainfall and temperature) to analyze it with SCA. The results revealed that SCA in Astore and Shigar has an increasing trend with a rate of 11.16 km2/year and 4.27 km2/year respectively. Mean annual precipitation and temperature also confirmed the increasing trend of SCA because mean annual precipitation is increasing and temperature is decreasing in both regions. SCA and elevation analysis revealed that SCA is decreasing on foothills while increasing at the valley top. Because temperature is increasing and precipitation is decreasing from zone 1 to zone 3 and vice versa for zone 4. It is found that Astore and Shigar in UIB have an increasing trend of SCA and does not affect by global warming. Therefore, it is necessary to conduct studies on large scale to efficiently evaluate the impact of climate on SCA.